مۆدێلە تیۆرییەكانی شیكردنەوهی پەیوهندیی پاشخانی كۆمەاڵیەتی بە - Muhammes Hussain Sjwani; Jalal Ahmed Abdullah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
T h i s s t u d y d i s c u s s e s t he o r e t i c a l l y t he r e l a t i o n s h i p be t we e n i n di v i d ua l s ’ s o c i a l b a c k g r o u n d a n d t he i r p a r t i c i p a t i o n i n p ol i t i c s , t h a t ' s i n t he l i g h t o f t he t he o r e t i c a l mo de l s o f t he s o c i o- e c o n omi c s t a t u s , a n d t he r e s o u r c e s o f p o l i t i c a l p a r t i c i p a t i o n. T he f i r s t mo de l e mp ha s i z e s o n t he e x i s t i n g p o s i t i v e r e l a t i o n s hi p be t we e n i n di v i d ua l s p a r t i c i p a t e i n p o l i t i c s a n d t he i r e d u c a t i o na l l e v e l , o c c u p a t i o n a n d i n c ome ; Al s o T he s e c o n d mo de l f o c u s u p o n t he p o s i t i v e r e l a t i o n s h i p o f t he p o s s i b i l i t y o f d o na t e ( mo ne y ) , t i me a n d c i v i l s k i l l s wi t h i n di v i d u a l ’s i n v o l v e me n t i n p ol i t i c s . Wh i l e Ac c o r d i ng t o t he r e s u l t s o f t h i s s t u d y , t he r e i s a r e l a t i o n s hi p be t we e n i n di v i d u a l s ’ s o c i a l ba c k g r o u n d a n d t he i r pa r t i c i pa t i ng i n p o l i t i c s , f i n d i ng s F r om t he p r a c t i c a l t e s t s o f t he mo de l s me n t i o ne d r e p o r t e d t h a t t he t y pe a n d di r e c t i o n o f t he r e l a t i o n s hi p be t we e n t he t wo v a r i a bl e s , a r e r e l a t i v e a n d i n di r e c t ; s o t he i n di v i d u a l ' s p ol i t i c a l pa r t i c i pa t i o n i n e a c h c ommu n i t y di f f e r s a c c o r d i ng t o t he f o r ms o f p a r t i c i pa t i o n, de mo g r a p h i c v a r i a bl e s , a n d t he s o c i oe c o n omi c s t a t u s a n d p o l i t i c a l c i r c ums t a n c e . P r o ba b l y , t he l e v e l o f e d u c a t i o n , i n c ome a n d o c c u pa t i o n i n d i f f e r e n t s i t ua t i o n s a n d s o c i e t i e s , d oe s n o t h a v e a p o s i t i v e i mpa c t o n p a r t i c i p a t i o n i n a l l p o l i t i c a l a c t i v i t i e s , i n s ome s o c i e t i e s a n d s pe c i a l s i t ua t i o n s , l o w l e v e l o f s o c i oe c o n omi c s t a t u s , f a mi l y r e l a t i o n s a n d p r o x i mi t y , ne t wo r k s f o r p o l i t i c a l mo bi l i z a t i o n, r e f l e c t s p o s i t i v e l y o n t he t y pe a n d d i r e c t i o n o f p o l i t i c a l pa r t i c i p a t i o n o f i n di v i d u a l s . I n g e ne r a l , i t a p pe a r s t h a t t he d oma i n a n d t he e q u a l o p p o r t u n i t y f o r p o l i t i c a l p a r t i c i pa t i o n , r e q u i r e s n o t onl y t he p o l i t i c a l a n d l e g a l s t r u c t u r e , but a l s o t he s i mi l a r i t i e s i n t he l i v i ng c o n di t i o n s a n d pe o p l e s s o c i oe c o n omi c s t a t u s wi t h t he ne c e s s a r y r e s o u r c e s f o r a c t i v e p a r t i c i pa t i o n i n p o l i t i c s .